Angola : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Angola. (IMF Staff Country Reports; Country Report ;, 2017)
This 2016 Article IV Consultation highlights that the oil price shock that started in mid-2014 has substantially reduced Angola's fiscal revenue and exports. Growth was estimated to come to a halt in 2016, with the nonoil sector contracting by 0.5 percent, dragged down by the industrial, construction, and services sectors. Industrial production, despite the potential for import substitution, was constrained by shortages of imported inputs owing to limited availability of foreign exchange. The current account deficit, which peaked at 10 percent of GDP in 2015, is projected to be halved in 2016-17, as imports continue adjusting to limited availability of foreign exchange.